KARAKTERISTIK PEDAGANG, SANITASI PENGOLAHAN DAN ANALISA KANDUNGAN RHODAMIN B PADA BUMBU CABAI GILING DI PASAR TRADISIONAL KECAMATAN MEDAN BARU TAHUN 2012 - Berta Kartina; Taufik Ashar; Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2012)
Characteristics of Trader, Sanitation Processing and Analysis Content of Rhodamin B in Seasoning Chili Double-Milled in Traditional Market Sub-district Medan Baru in 2012. Rhodamin B is one of synthetic dyestuff commonly used as textile dyes are not allowed to use in food products. But there is still a trader who uses rhodamin B in food and beverage products. Seasoning chili double-milled is one of ingredient that is a result of grinding red chili until smooth. The housewife uses seasonings chili double-milled because it easy to use, cheap and time-saving. The purpose of this research was to know dyes rhodamin B in seasoning chili double-milled in traditional market sub-district Medan Baru in 2012, knowing characteristics of trader, the level of knowledge and sanitation processing seasoning chili double-milled. This research was a simple descriptive. The method used was applicable in the examination of laboratory in seasoning chili double-milled with chromatography paper and interview using a questionnaire to 11 traders in traditional market sub-district Medan Baru. Based on the observation known that the sanitary processing of seasoning chili double-milled did not meet the health requirement. The results of the laboratory examination known that all (100%) seasoning chili double-milled does not contain rhodamin B. The results of questionnaire showed that traders with knowledge of enough category as many as 8 (72.7%), traders with knowledge of good category as many as 2 (18.2%) and traders with knowledge of less category as many as 1 (9.1%). It was recommended to traders to pay more attention to sanitation processing and more wisely in choosing dye substance will be used and to the government to more tighten supervision and checks periodically on seasoning chili double-milled so there was no use dye substances not allowed as rhodamin B. Keywords : Rhodamin B, Seasoning chili double-milled, Trader of seasoning chili double-milled